Pengaruh Social Media Marketing Dan Kualitas Layanan Terhadap Keputusan Pembelian Efek Dengan Minat Beli Sebagai Variabel Intervening Pada Aplikasi Kisi Sekuritas Di Kota Padang - Aisyatur Rahmi; Vicky Brama Kumbara; Nia Nadilla (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This study aims to determine the influence of social media marketing and service quality on securities purchasing decisions, with purchase intention as an intervening variable among KISI Sekuritas application users in Padang City. The research method used was Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach using SmartPLS 3.0 software. The data collection technique was carried out by distributing questionnaires to 100 respondents who were users of the KISI Securities application in Padang City.The data analysis results indicate that social media marketing has a positive and significant effect on securities purchasing decisions, and service quality has a positive and significant effect on securities purchasing decisions. In addition, purchasing interest has a positive and significant influence on the decision to purchase securities. The results of the study also show that social media marketing has a positive and significant effect on purchasing interest, while service quality does not have a significant effect on purchasing interest. Furthermore, the results of the intervening variable test indicate that purchase intention mediates the influence of social media marketing on securities purchasing decisions, but not the influence of service quality on securities purchasing decisions.Based on the research results, it can be concluded that social media marketing plays a significant role in increasing purchasing interest and securities purchasing decisions among KISI Securities app users in Padang City, while service quality plays a more direct role in securities purchasing decisions.